Intelligent System for Soccer Referee’s Position Analysis - Rego, Carlos Moreira (2019)
The role of referees and the decisions they take have, in many cases, a decisive and direct influence on the course of a game. Unfortunately these decisions are not always correct. In a large amount of times, the mistakes are due to referee’s bad positioning on the field. So it is fundamental to develop a model that may determine the correct position for a soccer referee. For this research work, data with all the game participants’ positions in the field during the match has been used as its basis. The data included, players, ball and referees positions gathered by an automatic system. Referees with large experience in international competitions were used to obtain correct position knowledge. The achieved results, using a data mining approach, are very positive, both for predicting the assistant referee position, regardless of the team he is accompanying or the match with 77 % of success, as to predict the referee position with 82 % of success, in controlled game situations. In short, despite the limitations, the models are conclusive and can efficiently estimate the correct positioning of the referee in a soccer match.